Relationship between Workgroup Emotional Climate (WEC) and Knowledge Sharing in the Knowledge-Based Companies of Iran - Mahmood Noori, Xiao-Yu Liu, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research was conducted to investigate the effect of workgroup emotional climate (WEC) on knowledge sharing in the knowledge-based companies of Iran. The research ahead is applied and its approach is descriptive-survey. In this research, senior and middle managers of the knowledge-based companies of north Khorasan province in Iran were considered as statistical population, the number of whom was 250 people. Based on the Cochran's formula, 148 statistical samples were required for this population. In the present research, the available stratified sampling method has been used to select statistical samples. The research data collection tool was a researcher-made questionnaire consisting of two standard questionnaires containing 20 items in themselves. The validity of this questionnaire was investigated and confirmed through face validity and confirmatory factor analysis methods. The reliability of the questionnaire was also investigated and confirmed by Cronbach's alpha method. The data obtained from the questionnaires were analyzed using descriptive and inferential methods and through SPSS and LISREL software. At the end, the research results showed that in the population under study, WEC has a significant impact on knowledge sharing.